2018
DOI: 10.4274/balkanmedj.2017.0487
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza Vaccine Effectiveness in Preventing Laboratory Confirmed Influenza in 2014-2015 Season in Turkey: A Test-Negative Case Control Study

Abstract: Background:Influenza has an important public health impact worldwide with its considerable annual morbidity among persons with or without risk factors and its serious complications among persons in high-risk groups. The seasonal influenza vaccine is essential for preventing the burden of influenza in a population. Since the vaccine is reformulated each season according to the virus serotypes in circulation, its effectiveness can vary from season to season. Vaccine effectiveness is defined as the relative risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…There are very few reports about influenza vaccination rate in Turkey and vaccination ratio change between 5% and 27% in adult studies 27–29 . Overall influenza vaccination coverage rate was 4.2% according to data of Public Health Institute of Turkey, which is really not sufficient to control the burden of infleunza, 30 although the Global Influenza Hospital Surveillance Network included pediatric cases from Turkey reported that vaccination seemed to confer better protection against influenza B and in children under 4 years of age and prevent approximately one in four hospitalizations with influenza 31 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are very few reports about influenza vaccination rate in Turkey and vaccination ratio change between 5% and 27% in adult studies 27–29 . Overall influenza vaccination coverage rate was 4.2% according to data of Public Health Institute of Turkey, which is really not sufficient to control the burden of infleunza, 30 although the Global Influenza Hospital Surveillance Network included pediatric cases from Turkey reported that vaccination seemed to confer better protection against influenza B and in children under 4 years of age and prevent approximately one in four hospitalizations with influenza 31 …”
Section: Discussionmentioning
confidence: 96%
“…nation coverage rate was 4.2% according to data of Public Health Institute of Turkey, which is really not sufficient to control the burden of infleunza,30 although the Global Influenza Hospital…”
mentioning
confidence: 98%
“…33 Overall, influenza vaccination coverage rate was 4.2% in Turkey according to data of the Public Health Institute of Turkey. 34 Influenza is still not included in the national immunization schedule of Turkey. Unfortunately, no other information related to the vaccination of the patients in this study was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Dari kelima negara, vaksin yang banyak digunakan adalah Trivalent Inactivated Vaccine (TIV). Persentase keefektivan vaksin untuk tipe virus influenza untuk tipe A genotip H1N1 bekisar 54,00% -68,40% dinilai efektif, untuk tipe B bekisar 34,00% -75,00% dinilai efektif tetapi untuk anak -anak di negara bagian Amerika Latin hanya 3% dinilai kurang efektif, dan untuk tipe A genotip H3N2 adalah 43,00% -65,00% dinilai efektif tetapi di negara Thailand pad atahun 2015/2016 sebesar 2% dinilai kurang efektif [16,17,18,19,20]. Keefektivan vaksin ini terjadi pada banyaknya kasus pada tipe -tipe influenza yang terjadi di negara itu, bahwa kasus H1N1 lebih banyak daripada H3N2 jadi dimungkinkan keefektivan vaksin terhadap H3N2 kurang efektif dari H1N1.…”
Section: Bahasanunclassified